Jaarverslag 1971 : Provinciale Dienst voor Cultuur. (Brugge : Provincie West-Vlaanderen, 1972)
Hoorne, Emiel ; Kuyle, Ghislain ; Gheyssens, Moniek ; Huybrechts, Marie-Christine ; Schotte, Monique ; Vandekerckhove, Rita ; Bogart, Bram ; Clarysse, Clarck ; Duchateau, Hugo ; Willaert, Joseph ; Withofs, Jan ; Decroubele, Luc ; Spilliaert, Pol ; Wierusz-Kowalski, Tapta
Nederlands
boek